Impact of Leadership Style on Organizational Performance: A Nepalese Commercial Bank - Chaudhary, Priyanshu (Nepalese Journal of Economics, 2025)
This study examines the impact of leadership style on organization in Nepal. Organizational performance is the dependent variable. The selected independent variables are charisma, inspirational motivation, intellectual stimulation, constructive reward, and management by expectation. The primary source of data is used to assess the opinions of respondents regarding charisma, inspirational motivation, intellectual stimulation, constructive reward, and management by expectation and organizational performance. The study is based on primary data of 151 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of leadership style on organizational performance in Nepalese commercial bank. The study showed that charismatic leadership is positively correlated to organizational performance. It indicates that better charismatic leadership, leads to better organizational performance. Similarly, inspirational motivation is positively related to organizational performance indicating that higher the level of inspirational motivation, higher would be the organizational performance. Likewise, intellectual stimulation has positive relationship with organizational performance. It shows that intellectual stimulation leads to an increase in the organizational performance. Similarly, constructive reward has positive relationship with organizational performance. It reveals that higher the level of constructive reward, higher would be organizational performance. The result shows that there is positive relationship between management by exception and organizational performance. It shows that an increase in the level of management by exception leads to the increase in the organizational performance.